Annealing studies on a thermotropic liquid crystalline polyester meltblown fabric - Koçer, Hasan Basri; Çerkez, İdris; Broughton, Royall M. (Sage Publications Inc, 2017)
Meltblown fabrics composed of a thermotropic liquid crystalline polyester were subjected to heat conditioning at various temperatures. Physical effect of the treatment was investigated by tensile testing of the fabrics and the individual fibers. The fabrics exhibited increased tensile strength by more than 100% after the heat conditioning due to inter-fiber bonding in the fabric structure and morphological reorganization of the thermotropic polymer. The calorimetric behavior of the polymer was further investigated to obtain information about the internal structure. Structural change during the annealing was also visually observed under a polarized light microscope.
Keywords: Meltblown; nonwoven; thermotropic; liquid crystalline; polyester